THE PRICE OF NON-COOPERATION IN RESERVATION-BASED BANDWIDTH SHARING PROTOCOLS - T. Dung, Tran; T. M. Trang, Truong (Vietnam Journal of Science and Technology, 2012)
ABSTRACTIn reservation-based bandwidth sharing protocols, the base station relies on the stations’ requests to allocate time slots to them. Like most  other protocols, reservation-based protocols were designed with the assumption that all stationsrespect the rules of the protocols. However, as mobile devices are becoming more intelligent andprogrammable, they can selfishly optimize their operations to obtain a larger share of commonbandwidth. Here, we study reservation-based bandwidth sharing protocols considering the existence of selfish stations through game-theoretic perspectives. We show that this game admits a Nash  equilibrium. Then, we prove the inefficiency of the Nash equilibrium. Game-theoretical analysis shows that local optimization in the bandwidth sharing problem with conflicted interests does not lead to any global optimization.Keywords. Nash equilibrium, Repeated game, Reservation-based.